Seafloor vegetation map of man-made boulders reef by underwater photogrammetry: Suggestions for site selections in macroalgal bed creations - Takayuki Kanki; Wataru Sano; Masami Sannoh; Hironobu Kan (PLoS ONE, 2026)
Macroalgal beds play important roles in coastal ecosystems by supplying oxygen, providing food resources, and offering habitats for various marine animals. In recent years, macroalgal beds have significantly declined due to various factors, leading to efforts toward macroalgal bed restorations. Despite these efforts, suitable sites for macroalgal bed creations remain insufficiently understood. In this study, we investigated suitable location conditions for establishment of macroalgal beds by mapping the seafloor vegetation. In an 80 m × 20 m area at a depth of 4.5–9.2 meters in Himeshima Island, Fukuoka, Japan, man-made boulders reef was created by the local government in the fiscal year 2016 for macroalgal bed creation. A 3D model of the seafloor, with a resolution of 0.07 meters, was created using underwater photogrammetry, enabling the visualization of macroalgal vegetation on these artificial boulders through a detailed seafloor vegetation map. Rich macroalgal vegetation, including Sargassum spp. and Undaria pinnatifida was established on the boulders placed on sandy bottoms. In contrast, on the boulders placed on natural cobble/boulder reefs, only a short-lived seaweed Colpomenia sinuosa was observed, and almost all boulders showed no vegetation. Even on the sandy bottoms, boulders that were adjacent to or surrounded by natural cobble/boulder reefs, or those that were piled together, tended to have poor vegetation. For effective macroalgal beds creation, installation of boulders at a low density on sandy bottoms would be preferable, while avoiding the areas on or adjacent to natural cobble/boulder reefs.